Anomalous enhancement of atomic vibration induced by electronic transition in 2H-MoTe2 under compression. (28th October 2021) - Hao, Xingyu; Guo, Zhiying; Li, Haijing; Gong, Yu; Chen, Dongliang
Abstract: In this work, we explore the atomic vibration and local structure in 2H–MoTe2 by using high-pressure x-ray absorption fine structure spectroscopy up to ∼20 GPa. The discrepancy between the Mo–Te and Mo–Mo bond length in 2H–MoTe2 obtained from extended-XAFS and other techniques shows abnormal increase at 7.3 and 14.8 GPa, which is mainly due to the abrupt enhancement of vibration perpendicular to the bond direction. Ab initio calculations are performed to study the electronic structure of 2H–MoTe2 up to 20 GPa and confirm a semiconductor to semimetal transition around 8 GPa and a Lifshitz transition around 14 GPa. We attribute the anomalous enhancement of vibration perpendicular to the bond direction to electronic transitions. We find the electronic transition induced enhancement of local vibration for the first time. Our finding offers a novel insight into the local atomic vibration and provides a new platform for understanding the relationship between the electronic transition and atomic vibration.